1998
DOI: 10.2307/749715
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of Invention and Understanding in Children's Multidigit Addition and Subtraction

Abstract: This 3-year longitudinal study investigated the development of 82 children's understanding of multidigit number concepts and operations in Grades 1-3. Students were individually interviewed 5 times on a variety of tasks involving base-ten number concepts and addition and subtraction problems. The study provides an existence proof that children can invent strategies for adding and subtracting and illustrates both what that invention affords and the role that different concepts may play in that invention. About … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
103
0
14

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(119 citation statements)
references
References 13 publications
2
103
0
14
Order By: Relevance
“…Knowledge of multiple strategies has clear benefits for learning and performance; for example, learners with knowledge of multiple Prior knowledge and flexibility 5 strategies at pretest are more likely to learn from instructional interventions (Alibali, 1999;Siegler, 1995). In general, and across multiple domains (including elementary mathematics), the benefits of multiple strategies are well documented (Alibali, 1999;Carpenter, Franke, Jacobs, Fennema, & Empson, 1998;Dowker, 1998 Knowledge of strategy efficiency is a fundamental feature of problem-solving expertise and is also a fundamental mechanism supporting learning and development (Siegler, 1996). For example, Blöte and colleagues have found that more skilled students know and select mental addition strategies that most closely match the characteristics of numbers in the problem, because such a matching approach allowed students to solve the problem using the fewest number of steps (Blöte, Klein, & Beishuizen, 2000;Blöte et al, 2001).…”
Section: Flexibility: the Case Of Computational Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…Knowledge of multiple strategies has clear benefits for learning and performance; for example, learners with knowledge of multiple Prior knowledge and flexibility 5 strategies at pretest are more likely to learn from instructional interventions (Alibali, 1999;Siegler, 1995). In general, and across multiple domains (including elementary mathematics), the benefits of multiple strategies are well documented (Alibali, 1999;Carpenter, Franke, Jacobs, Fennema, & Empson, 1998;Dowker, 1998 Knowledge of strategy efficiency is a fundamental feature of problem-solving expertise and is also a fundamental mechanism supporting learning and development (Siegler, 1996). For example, Blöte and colleagues have found that more skilled students know and select mental addition strategies that most closely match the characteristics of numbers in the problem, because such a matching approach allowed students to solve the problem using the fewest number of steps (Blöte, Klein, & Beishuizen, 2000;Blöte et al, 2001).…”
Section: Flexibility: the Case Of Computational Estimationmentioning
confidence: 99%
“…Knowledge of multiple strategies has clear benefits for learning and performance; for example, learners with knowledge of multiple Prior knowledge and flexibility 5 strategies at pretest are more likely to learn from instructional interventions (Alibali, 1999;Siegler, 1995). In general, and across multiple domains (including elementary mathematics), the benefits of multiple strategies are well documented (Alibali, 1999;Carpenter, Franke, Jacobs, Fennema, & Empson, 1998;Dowker, 1998;LeFevre, Smith-Chant, Hiscock, Daley, & Morris, 2003;Resnick & Ford, 1981;Rittle-Johnson & Star, 2007;Star & Rittle-Johnson, 2008, in press;Star & Seifert, 2006).…”
mentioning
confidence: 99%
“…The ability to flexibly solve math problems is a valued measure of proficiency and important to future learning [5,8]. Few studies have investigated how strategic flexibility is displayed in ITSs, and perhaps as a result no studies have directly measured math flexibility using an ITS.…”
Section: Discussionmentioning
confidence: 99%
“…Schneider et al [2] found a bidirectional relationship between procedural and conceptual knowledge and hypothesized that these two types of knowledge improve strategic flexibility in an iterative fashion. Students who have high strategic flexibility are more likely to adapt their strategies, transferring their knowledge to solve new problems [8,4]. Conversely, students who lack strategic flexibility struggle to solve more difficult or unfamiliar problems that require the use of different strategies [6].…”
Section: Introductionmentioning
confidence: 99%
“…These four features of multiple-strategy instruction, along with the two types of instructional goals, emerged from research around the learning and teaching of mathematics in elementary school, particularly the work of the Cognitively Guided Instruction (CGI) project (e.g. Carpenter, Franke, Jacobs, Fennema, & Empson, 1998) combined with an emphasis on the use of multiple representations in algebra (e.g., Brenner et al, 1997;Star & Rittle-Johnson, 2009b).…”
Section: Multiple Strategiesmentioning
confidence: 99%